Microflocculation Assay for Gonococcal Antibody - Reising, Gilbert (1971)
An antigen suspension consisting of cholesterol-lecithin particles sensitized with an extract of gonococci was used in a flocculation assay for the detection of human antibodies to Neisseria gonorrhoeae. With culturally and clinically diagnosed cases of uncomplicated gonorrhea, sera from 70 (49.6%) of 141 males and 207 (79.0%) of 262 females were reactive in the assay. Sera from four (7.3%) of 55 males and 11 (5.4%) of 203 females, all presumed normal, were reactive. The assay utilized equipment available in most clinical and public health laboratories.